2018
DOI: 10.5812/ijp.65396
|View full text |Cite
|
Sign up to set email alerts
|

Motor Performance and Activities of Daily Living in Children with Neurodevelopmental Disorders

Abstract: Background: Neurodevelopmental disorders (NDDs) are developmental deficiencies that arise due to the damage of the central nervous system in the prenatal, natal, or postnatal period. Objectives: The aim of this study was to evaluate the motor performance and activities of daily living (ADL) and examine their relationship in children with NDDs who do not have physical disabilities. Methods: A total of 107 children who were diagnosed with NDDs, without physical disabilities, and 36 healthy peers between the ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In addition to static movements in the physical activity of the sandsack, there is dynamic movement of the ability to maintain body position in changing COG, dynamic balance causes automatic postural adjustment to maintain posture and stability in various conditions and movements (Volkan-Yazici et al, 2018). As is done in the physical activity of this sandsack, the movement of shifting and kicking positions, walking from point to point and jumping and walking backward is done sequentially Jurnal Keterapian Fisik Vol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to static movements in the physical activity of the sandsack, there is dynamic movement of the ability to maintain body position in changing COG, dynamic balance causes automatic postural adjustment to maintain posture and stability in various conditions and movements (Volkan-Yazici et al, 2018). As is done in the physical activity of this sandsack, the movement of shifting and kicking positions, walking from point to point and jumping and walking backward is done sequentially Jurnal Keterapian Fisik Vol.…”
Section: Discussionmentioning
confidence: 99%
“…Neurodevelopmental conditions that affect a child’s typical development are present in approximately 9% of school-aged children in Spain [ 9 ]. These children usually face more performance difficulties and participation restrictions than their TD peers, which might have further consequences on their emotional and psychological wellbeing [ 20 , 21 , 22 , 23 , 24 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. To the best of our knowledge, no studies on NDDs have so far compared participation restrictions in the different daily contexts in Spanish children with and without NDDs.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings in these contexts are in line with previous studies that explored children from Europe, America, and Asia, which is of particular interest given that self-care and home maintenance activities may be different between cultures. Self-care and instrumental activities are one of the most problematic contexts for children with ASDs, ADHD, and DCD [ 21 , 24 , 33 , 35 ]. In addition, van der Linde et al found that children with DCD both participated significantly less and performed significantly worse than TD children in self-care activities, while daily performance and participation were interrelated as performance predicted participation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations